Study on SMEs of the FNB Industry to Examine the Relationship between Management Skill, Financial Resource Availability, and Product Quality Toward Business Success - Novela, Selly; Yollanda, Zoeleika (International Review of Management and Marketing, 2026)
Strong internal capability enables SMEs to implement strategies effectively, adapt, and maintain consistent quality without excessive reliance on external parties. In increasingly dynamic markets, internal capability allows SMEs to respond proactively to environmental uncertainty and changing customer demands. This study examines the role of internal capability in SME success, focusing on management skills, financial resource availability, and product quality. These factors are considered critical as they directly influence operational efficiency, innovation capacity, and customer satisfaction. The research addresses a gap in prior studies that have largely emphasized SME performance rather than broader success indicators such as sustainability and growth potential. An associative research design with a quantitative approach was employed. Data were collected through an online questionnaire, yielding 249 valid responses. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that management skills, financial resource availability, and product quality have a significant positive effect on SME success, confirming all proposed hypotheses. These findings suggest that SMEs should strengthen managerial competencies, manage cash flow efficiently, and continuously improve product quality to achieve sustained business success and enhance their competitive position.